2017
DOI: 10.1080/10810730.2017.1341565
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Informed Consent Materials: Designed for Documentation, Not Comprehension of Health Research

Abstract: Minority populations with health disparities are underrepresented in research designed to address those disparities. One way to improve minority representation is to use community-based participatory methods to overcome barriers to research participation, beginning with the informed consent process. Relevant barriers to participation include lack of individual or community awareness or acceptance of research processes and purposes. These barriers are associated with limited health literacy. To inform recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
0
22
0
5
Order By: Relevance
“…One obvious and refl exive approach to mitigating these is to embed them in informed consent documents. Unfortunately, consent forms are often poorly understood [31] and poorly recalled [32]; they can often appear to be exercises in liability mitigation rather than clear explanations of experimental procedures designed with the patient or research participant in mind [33,34,35]. Eff orts to optimize consent for genomics-based screening programs should be pursued, particularly if included alongside other routine health screenings.…”
Section: Ethical Considerations For Genomics-based Screening Programsmentioning
confidence: 99%
“…One obvious and refl exive approach to mitigating these is to embed them in informed consent documents. Unfortunately, consent forms are often poorly understood [31] and poorly recalled [32]; they can often appear to be exercises in liability mitigation rather than clear explanations of experimental procedures designed with the patient or research participant in mind [33,34,35]. Eff orts to optimize consent for genomics-based screening programs should be pursued, particularly if included alongside other routine health screenings.…”
Section: Ethical Considerations For Genomics-based Screening Programsmentioning
confidence: 99%
“…A wealth of recent publications describing consent in human clinical trials has focused on readability and comprehension of medical consent forms . A survey conducted by the National Assessment of Adult Literacy concluded that approximately half of Americans have only basic literacy skills and that 14% have literacy skills that are less than basic .…”
Section: Introductionmentioning
confidence: 99%
“…23 Based on the evidence presented in this literature review, clinical trial consents are often written above the average health literacy level, prohibiting patients from being able to fully understand what they are signing. 21 Several of the articles presented the use of modified or simplified consents to aid in this process in order to attempt to increase comprehension levels among all patients. 7,14,13 Comprehension improved when information was simplified, increasing patients' satisfaction and confidence in their decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Simonds et al 21 assessed 97 informed consent documents to determine readability, suitability, and comprehensibility. By using the Simple Measure of Gobbledygook, the results showed that the average reading level of the consents was grade 12.…”
Section: Health Literacy and Patient Comprehension Of Informed Consenmentioning
confidence: 99%